PENGARUH TIME BUDGET PRESSURE, LOCUS OF CONTROL DAN PERILAKU DISFUNGSIONAL AUDIT TERHADAP KINERJA AUDITOR (STUDI PADA KANTOR AKUNTAN PUBLIK INDONESIA) - Maya Febrianty Lautania (Program Magister Akuntansi Unsyiah, 2011)
This research performed at Public accountant Office (CAP) which is distributed in some province in Indonesia, with aim of the reserach is to know influence Time Budget Pressure, Locus of Control and dysfunctional audit behavior to auditors performance which works for public accountant Office of parsial influence or simultaneously.Responden in this research is auditors at Public Accountant office which is registered in Institute Akuntan Publik Indonesia (IAPI). This research type has the character of correlational with number of sample 91 auditor from population a number of 998 inscribed CAP auditor which is random chosen within region based. Path analysis is used as a data analytical technique.Based on result of analysis it is concluded that Time Budget Pressure, Locus of Control and dysfunctional Audit Behavior has an effect on to Auditors Performance in simultaneously. Time budget pressure has an effect to auditors performance, locus of control has a insignificant negative effect to auditors performance and dysfunctional audit behavior has an effect to auditors performance. Keywords : Time Budget Pressure, Locus of Control, Dysfunctional audit behavior, auditors performance.